SpaceOAR to improve dosimetric outcomes for monotherapy high-dose-rate prostate implantation in a patient with ulcerative colitis - Trager, Michael; Greenberger, Benjamin; Harrison, Amy S; Keller, James; Den, Robert B (Journal of Contemporary Brachytherapy, 2018)
High-dose-rate (HDR) brachytherapy is an attractive option for patients receiving definitive radiation therapy for prostate cancer with decreased overall dose to the pelvis. However, ulcerative colitis increases rectal toxicity risk and may be a contraindication. A synthetic hydrogel, SpaceOAR (Augmentix Inc., Waltham, MA, USA), can facilitate the use of HDR brachytherapy for patients where rectal toxicity is a limiting factor. SpaceOAR gel (13.19 cc) was utilized in a monotherapy HDR prostate treatment with Ir-192 under transrectal ultrasound guidance, with the intention of decreasing rectal dose. SpaceOAR gel was inserted transperineally into the patient 18 days prior to the procedure. The HDR brachytherapy procedure was tolerated without incident. All planning constraints were met, and the following dosimetry was achieved: Prostate – V100% = 97.3%, V150% = 35%, V200% = 14.5%; Urethra – V118% = 0%; Rectum – D2 cc = 51.6%, V75% = 0 cc. The rectum-catheter spacing was on average between 6-8 mm. Average spacing for our 10 most recent patients without SpaceOAR was 3 mm. SpaceOAR did not hinder or distort ultrasound imaging or increase treatment time. SpaceOAR successfully increases catheter-rectal wall spacing and decreases rectal dose due to improved planning capabilities, while decreasing the likelihood of rectal perforation. One application of this tool is presented to mitigate potential toxicities associated with ulcerative colitis. At five months, one week, and one day follow-up, the patient reported no bowel issues following HDR brachytherapy.